2015
DOI: 10.3109/02699052.2015.1043344
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and gender influences on executive function following concussion in youth hockey players

Abstract: This study highlights the impact of age, gender and concussion on EF in youth. These findings provide foundational knowledge to better manage cognitive sequelae following sports-related concussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…There was strong evidence of a relationship between acute or subacute symptom burden and worse clinical outcome, although a few studies have not found this association (box 3).
Preinjury characteristics associated with recovery Younger age: Yes: Chermann81; Field82; Terwilliger83; Covassin84; Majerske85; Pellman86; Zuckerman71 No: Lau87; Hang30; McDevitt88; Nelson21; Asplund89; Chrisman75; Vargas74; Morgan58; Meehan42; Meehan90; Meehan6; McCrea91; Lee70; Baker92; Greenhill93; Nelson78; Corwin48; Preiss-Farzanegan94; Heyer80; Kontos67; Kriz77; Miller56, Ellis95; Gibson96 Female sex: Yes: Baker31; Berz97; Henry29, Kostyun79; Bock49; Zuckerman98; Covassin84; Covassin73; Covassin53; Majerske85; Colvin99; Eisenberg68; Ellis95; Miller56; Preiss-Farzanegan(in adults)94; Heyer80; Zemek57 No: Chermann81; Moor100; Hang30; Nelson21; Mayers101; Asplund89; Black72; Chrisman75; Zuckerman102; Zuckerman103; Vargas74; Terwilliger83; Morgan58; Frommer52; Baker92; McDevitt88; Nelson78; Lax104; Ono105; Preiss-Farzanegan (in children/adolescents)94; Covassin106; Kontos67; Wasserman41; Yang107; Meehan90; Gibson96; Meehan6 Race (non-white): Yes: Vargas74; Kontos
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was strong evidence of a relationship between acute or subacute symptom burden and worse clinical outcome, although a few studies have not found this association (box 3).
Preinjury characteristics associated with recovery Younger age: Yes: Chermann81; Field82; Terwilliger83; Covassin84; Majerske85; Pellman86; Zuckerman71 No: Lau87; Hang30; McDevitt88; Nelson21; Asplund89; Chrisman75; Vargas74; Morgan58; Meehan42; Meehan90; Meehan6; McCrea91; Lee70; Baker92; Greenhill93; Nelson78; Corwin48; Preiss-Farzanegan94; Heyer80; Kontos67; Kriz77; Miller56, Ellis95; Gibson96 Female sex: Yes: Baker31; Berz97; Henry29, Kostyun79; Bock49; Zuckerman98; Covassin84; Covassin73; Covassin53; Majerske85; Colvin99; Eisenberg68; Ellis95; Miller56; Preiss-Farzanegan(in adults)94; Heyer80; Zemek57 No: Chermann81; Moor100; Hang30; Nelson21; Mayers101; Asplund89; Black72; Chrisman75; Zuckerman102; Zuckerman103; Vargas74; Terwilliger83; Morgan58; Frommer52; Baker92; McDevitt88; Nelson78; Lax104; Ono105; Preiss-Farzanegan (in children/adolescents)94; Covassin106; Kontos67; Wasserman41; Yang107; Meehan90; Gibson96; Meehan6 Race (non-white): Yes: Vargas74; Kontos
…”
Section: Resultsmentioning
confidence: 99%
“…No: Chermann81; Moor100; Hang30; Nelson21; Mayers101; Asplund89; Black72; Chrisman75; Zuckerman102; Zuckerman103; Vargas74; Terwilliger83; Morgan58; Frommer52; Baker92; McDevitt88; Nelson78; Lax104; Ono105; Preiss-Farzanegan (in children/adolescents)94; Covassin106; Kontos67; Wasserman41; Yang107; Meehan90; Gibson96; Meehan6 …”
Section: Resultsmentioning
confidence: 99%
“…Unsurprisingly, concussion is more likely than other sports injuries to cause trouble with school work (Wasserman, Bazarian, Mapstone, Block, & van Wijngaarden, 2016) and a number of recent studies have reported an association between duration of concussion symptoms and academic problems (Baker, 2016;Field, Collins, Lovell, & Maroon, 2003;Ransom et al, 2015). Adolescents may be especially prone to school problems, as they take longer on average to recover from concussion than other age groups (Lax et al, 2015), and they usually have greater academic and extracurricular demands than younger children. Numerous authors have outlined suggestions for concussion-related academic accommodations (Halstead et al, 2013;Newlin & Hooper, 2015), and a graduated return-to-school strategy was created for the most recent consensus statement on concussion in sport (McCrory et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Executive function also seems to play a role in academic achievement and some researchers identify a definite difference between boys' and girls' executive function abilities, while others report that differences aren't significant. Blair, Raver and Berry (2013:560) (Lax et al 2015).…”
Section: Discussionmentioning
confidence: 99%